Stand-Alone Hardware Analytical System ААК12 for Detection of Geologic Faults in Coal Beds with the Use of Seismic Exploration in Mines - Antsiferov, A.V.; Tumanov, V.V.; Glukhov, A.A.; Arkhipenko, A.I. (Science and Innovation, 2024)
The general-circuit solutions for stand-alone hardware analytical system ААК12 have been described taking into account the safety measures for its implementation in mines. The performance capabilities of the main units and modules of the equipment have been considered for analogue and digital processing of recorded seismic signals, visualization and on-line analysis of the current measurements, as well as for data storage for further computer processing. The ААК12 basic technical specifications have been given.